'Upon the gears and upon the wheels': Terror convergence and total administration in the neoliberal university. Issue 4 (September 2020) - McCann, Leo; Granter, Edward; Hyde, Paula; Aroles, Jeremy
University governance is becoming increasingly autocratic as marketization intensifies. Far from the classical ideal of a professional collegium run according to academic norms, today's universities feature corporate cultures and senior leadership teams disconnected from both staff and students, and intolerant of dissenting views. This is not a completely new phenomenon. In 1960s America, senior leaders developed a technocratic and managerialist model of the university, in keeping with theories around the 'convergence' of socio-economic systems towards a pluralist 'industrial society'. This administrative-managerial vision was opposed by radical students, triggering punitive responses that reflected how universities' control measures were at the time mostly aimed at students. Today, their primary target is academics. Informed by Critical Theory and based on an autoethnographic account of a university restructuring programme, we argue that the direction of convergence in universities has not been towards liberal, pluralist, democracy but towards neo-Stalinist organizing principles. Performance measurements – 'targets and terror' – are powerful mechanisms for the expansion of managerial power or, in Marcuse's words, 'total administration'. Total administration in the contemporary university damages teaching, learning, workplace democracy and freedom of speech on campus, suggesting that the critique of university autocracy by 1960s students and scholars remains highly relevant.